Alcohol Use and STI among men in India: Evidences from a national household survey - Arvind Pandey; Ram Manohar Mishra; Dandu CS Reddy; Mariamma Thomas; Damodar Sahu; Deepak Bharadwaj (Wolters Kluwer Medknow Publications, 2012)
Background: Alcohol use has been found to correlate with risky sexual behavior as well as with sexually transmitted infections (STI) among populations with high-risk behavior in India. Objective: To examine the correlates of alcohol use and its association with STI among adult men in India. Materials and Methods: Data from a national representative large-scale household sample survey in the country were used. It included information on sociodemographic characteristics and alcohol use as a part of substance use. Clinical as well laboratory testing was done to ascertain the STI. Results: The overall STI prevalence among adult males was found to be 2.5% (95% confidence interval (CI): 1.9-3.1). Over 26% adult men were found to have been using alcohol in the study population. It was higher among men who were illiterate and unskilled industrial workers/drivers. The men who consumed alcohol had higher prevalence of STI (3.6%; 95% CI: 2.9-5.1) than those who did not consume alcohol (2.1%; 95% CI: 1.5-2.6). The degree of association between alcoholism and STI was slightly reduced after adjusting for various sociodemographic characteristics (adjusted odds ratio: 1.5; 95% CI: 0.9-2.3; P=0.06). Conclusions: The findings of present study suggest integrating alcohol risk reduction into STI/HIV prevention programmes.